Clinical Variant of Ablepharon Macrostomia Syndrome - Jose Larumbe; Patricia Villalta; Ines Velez (Case Reports in Dermatological Medicine)
Ablepharon syndrome is an extremely rare genetic problem that causes severe craniofacial deformities and numerous other abnormalities of the face, genitalia, and skin. The literature regarding this condition is scarce. We present a case of this syndrome with dental manifestations, not reported before, and discuss its characteristics in order to increase the knowledge of this condition among the dental profession.